2021
DOI: 10.3390/ijerph18084041
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Falls among Older Outpatients

Abstract: Falls in older people are a major public health issue, as they are associated with increased risks of morbidity and mortality. This study aims to investigate the prevalence and factors associated with falls among older outpatients. A cross-sectional study was conducted in 539 outpatients aged 60 and over at the National Geriatric Hospital, Hanoi, Vietnam. Falls and their associated factors were analyzed by multivariable logistic regression. The prevalence of falls was 23.7% (single fall 17.9%, recurrent falls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 50 publications
0
44
0
1
Order By: Relevance
“…Our study found that 23.1% of older adults visiting geriatric clinics experienced falls in the community during the two severe COVID-19 outbreaks. Since the prevalence of falls among Vietnamese geriatric outpatients before the pandemic was 23.7%, 16 our results suggest that there was no trend of increasing falls in this population during the pandemic.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Our study found that 23.1% of older adults visiting geriatric clinics experienced falls in the community during the two severe COVID-19 outbreaks. Since the prevalence of falls among Vietnamese geriatric outpatients before the pandemic was 23.7%, 16 our results suggest that there was no trend of increasing falls in this population during the pandemic.…”
Section: Discussionmentioning
confidence: 54%
“…A previous study showed that falls occurred in 23.7% of older outpatients in Vietnam. 16 Therefore, the required sample size for this study was a minimum of 810 participants with an allowable margin of error of 5%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most countries, the life expectancy growth rate has not been met by an increase in healthy life years [1][2][3][4][5]. With ageing, a growing prevalence of multiple comorbidities, chronic diseases, balance disorders and falls affecting the independence of the elderly has been observed [6][7][8][9][10][11]. However, healthy ageing does not mean disease-free.…”
Section: Introductionmentioning
confidence: 99%
“…Elderly falls represent an important public health problem, being the main cause of accidental death in the population over 65 years of age [ 1 , 8 , 9 , 10 ]. Although Portugal has one of the lowest rates of fall-related mortality in the elderly population of the Western European region, this issue has received attention from the Portuguese government [ 11 ].…”
Section: Introductionmentioning
confidence: 99%